(untitled) (Perner’s Contacts, 2017)
The article discusses the change of siding technology for a fossil fuel power plant using a new reloading system of Innofreight containers. This is a modern system for transporting thermal coal in special transport units – Innofreight containers. The assessment of the new technology takes into account not only technical, but above all technological and economic changes and benefits.